Impacts of functional literacy on the health of the elderly with medication adherence: integrative review (Research, Society and Development, 2023)
Objective: To evaluate in the scientific literature the relationship between Functional Health Literacy in the elderly and medication adherence. Method: integrative literature review, with search in online databases: Scientific Electronic Library Online (SCIELO); Virtual Health Library (VHL); Latin American and Caribbean Literature in Health Sciences (LILACS); Medical Literature Analysis and Retrieval System Online (MEDLINE); and Cumulative Index to Nursing & Allied Health Literature (CINAHL), between August 2021 and April 2022. Ten articles that met the inclusion criteria were selected. Results: Inadequate Functional Health Literacy makes a significant contribution to non-adherence to medication, however there are strategies and interventions that can be used to adapt care according to the needs and resources of each individual and thus reverse this relationship. Conclusion: Knowing the level of FHL in which the patient is is fundamental to know the right strategies to be used and in order to awaken in him a better vision of his clinical conditions and to do the therapy correctly.